Perspectives, benefits and challenges of a live OSCE during the COVID-19 pandemic in a cross-sectional study - Anne Herrmann-Werner; Teresa Loda; Rebecca Sarah Erschens; Stephan Zipfel; Andrew B Nevins (BMJ Open)
Objectives Restrictions due to the COVID-19 pandemic mandated fundamental changes to student evaluations, including the administration of the observed structured clinical examination (OSCE). This study aims to conduct an in-person OSCE to verify students’ practical skills under necessary infection control practices and the impact of face masks on student–patient interactions.Design Cross-sectional design.Setting The OSCE at Medical School of Tuebingen takes place in October 2020.Participants A total of 149 students (third year of study) completed the survey (RR=80.1%). It was their first OSCE.Primary and secondary outcome measures Primary outcome measure was how this type of OSCE was evaluated by participating students in regard to preparation, content and difficulty as well as in real life. Secondary outcome measures were how the implemented hygiene actions influenced the OSCE, including the interaction and communication between students and standardised patients (SPs). Items were rated on a 6-point Likert scale (1=completely to 6=not at all). Means, SDs, frequencies and percentages were calculated.Results 149 students, 32 SPs and 59 examiners participated. The students rated the OSCE with 2.37 (±0.52) for preparation and 2.07 (±0.32) for content. They perceived the interaction to be significantly disrupted by the use of face masks (3.03±1.54) (p<0.001) compared with the SPs (3.84±1.44) and the examiners (4.14±1.55). In general, the three groups considered the use of face masking the OSCE to be helpful (1.60±1.15).Conclusions An in-person OSCE, even in the midst of a global pandemic, is feasible and acceptable to both students and faculty. When compared the students’ results to previous students’ results who completed the OSCE before the pandemic, the results indicated that students felt less prepared than under non-pandemic circumstances; however, their performances on this OSCE were not lower.